Readiness to Apply SAK EMKM to UMKM - Widia Rahma Daienengsih; Andy Lasmana; Farizka Susandra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Conformity of financial reports with SAK EMKM will make it easier for UMKM actors to carry out various business activities. This study focuses on determining the effect of education level, understanding of accounting, and readiness of UMKM players on the application of SAK EMKM to UMKM in Bogor City. This study uses quantitative research with field study methods. The population in this study were SMEs registered with the Bogor City Cooperatives and SMEs Service, which consisted of 61,785 UMKM. The sample used in this study amounted to 100 samples using simple random sampling method. The results showed that the effect of education level, understanding of accounting, and the readiness of UMKM players simultaneously had a significant effect. While partially the level of education affects the application of SAK EMKM, understanding of accounting affects the application of SAK EMKM, and the readiness of UMKM actors does not affect the application of SAK EMKM.